Effect of Customer Value and Experiential Marketing to Customer Loyalty with Customer Satisfaction as Intervening Variable (Case Study on Gojek Makassar Consumers) - Abadi, Rahmat Riwayat; Nursyamsi, Idayanti; Syamsuddin, Andi Reni (School of Business and Management Institut Teknologi Bandung, 2020)
Abstract. The rapid growth in computer, technology, telecommunications, information and transportation has a big impact on companies to deliver a value and experience for customers. Companies are competing to offer excellent service for consumers, because consumers will satisfaction and encourage customers to be loyal. However, in reality there are deficiencies arising from online-based transportation systems. Complaints also varied, ranging from the application system or the driver. The research aimed at examining and analyzing the effect of customer value and experiential marketing on consumer’s loyalty with consumer’s satisfaction as intervening variable. The analysis units were the users of Gojek transportation service in Makassar city. Sampling in this study uses a purposive sampling method to get samples that fulfill the research criteria. The data were obtained using questionnaires. They were analyzed using Partial Least Square (PLS) processed with Smart PLS 3.0 program. The results of the research indicate that customer value positive and significantly affects costumer’s satisfaction and loyalty. Experiential marketing positive and significantly affects costumer’s satisfaction and loyalty. Costumer’s satisfaction positive and significantly affects costumer’s loyalty. Customer value and experiential marketing positive and significantly affects costumer’s loyalty through costumer’s satisfaction.Keywords: Customer Loyalty, Customer Satisfaction, Customer Value, Experiential Marketing, and Transportation